Impact of Financial Literacy on University Students' Entrepreneurial Orientation in Khulna City - Jarif Hossain; Farhana Amin Kona; Zona Zaman (Goodwood Publishing, 2026)
Purpose: This study aims to examine the relationship between financial literacy and entrepreneurial orientation among university students in Khulna City, Bangladesh. Methodology: This quantitative study collected primary data from 250 students across public and private universities in Khulna, Bangladesh, using stratified and convenience sampling. A self-administered questionnaire with a 5-point Likert scale was used to collect data. The data were analyzed using correlation and regression techniques. Results: The results indicate a significant positive correlation of .807 between financial literacy and entrepreneurial orientation. The regression analysis shows that financial literacy has 35.5% explanatory power on entrepreneurial orientation. Conclusions: This study demonstrates that financial literacy significantly enhances students’ entrepreneurial orientation, explaining 35.5% of its variance. The findings highlight the importance of integrating financial education into higher education to support entrepreneurship and economic growth. Limitations: The primary limitation of this study is its sample size, with most respondents from Khulna University. Data collection was conducted online, and broader participation required more time and resources. Contributions: Overall, the findings suggest that improving university students' financial literacy can play a pivotal role in strengthening their entrepreneurial orientation, contributing to a more dynamic and resilient economy.